Assessing Antioxidant Capacity in Brain Tissue: Methodologies and Limitations in Neuroprotective Strategies - Jennifer E. Slemmer; John T. Weber (MDPI AG, 2014)
The number of putative neuroprotective compounds with antioxidant activity described in the literature continues to grow. Although these compounds are validated using a variety of in vivo and in vitro techniques, they are often evaluated initially using in vitro cell culture techniques in order to establish toxicity and effective concentrations. Both in vivo and in vitro methodologies have their respective advantages and disadvantages, including, but not limited to, cost, time, use of resources and technical limitations. This review expands on the inherent benefits and drawbacks of in vitro and in vivo methods for assessing neuroprotection, especially in light of proper evaluation of compound efficacy and neural bioavailability. For example, in vivo studies can better evaluate the effects of protective compounds and/or its metabolites on various tissues, including the brain, in the whole animal, whereas in vitro studies can better discern the cellular and/or mechanistic effects of compounds. In particular, we aim to address the question of appropriate and accurate extrapolation of findings from in vitro experiment-where compounds are often directly applied to cellular extracts, potentially at higher concentrations than would ever cross the blood-brain barrier-to the more complex scenario of neuroprotection due to pharmacodynamics in vivo.